Aspirational intimacy in visiting friends and relatives. (May 2022) - Humbracht, Michael; Cohen, Scott; Williams, Allan M.
Abstract: Tourism research on visiting friends and relatives remains normative and family-centric. The literature has yet to question the normative underpinnings of relationships and remains oriented around physical proximity. This paper therefore aims to understand the shifting qualities and intimacies of migrant personal relationships developed across diverse means for maintaining relationships. It draws from a multi-sited ethnography that includes interviews from migrants and friends and family living at a distance. Framed through theory on personal relationships and affect, we introduce the concept 'aspirational intimacy'. This shows how important relationships become oriented around aspirations of normalcy and belonging that construct shared capacities to feel connected, while imagining alternative possibilities for relationships and life-course trajectories. Highlights: De-centres the family and physical proximity in tourism research on migrant visits Develops the concept of aspirational intimacy to conceptualize transnational relationships Draws from a multi-sited ethnography that includes interviews with migrants and friends and family Utilizes the relationship mapping technique from the sociology of personal life